Handbook of numerical and statistical technique with examples mainly from life sciences - Pollard, J.H. (Cambridge University P. CambridgeGB, 1977)
The three sections of this book deal with numerical techniques, statistical techniques, and the method of least suqares respectively. Shows how each calculation is performed and illustrates each technique with examples.